The endothelial NO synthase content in the blood serum of patients with coronavirus disease (COVID-19) with pneumonia in association with hemostatic parameters depending on the clinical course and its prognostic significance - Riabokon, O. V.; Kuliesh, I. O.; Bielenichev, I. F.; Riabokon, Yu. Yu.; Рябоконь, Олена Вячеславівна; Кулєш, І. О.; Бєленічев, Ігор Федорович; Рябоконь, Юрій Юрійович (Запорізький державний медико-фармацевтичний університет, 2024)
Aim: to investigate the content of eNOS in the blood serum of patients with coronavirus disease (COVID-19) with pneumonia in association with hemostatic parameters and to determine its prognostic value in assessing the risk of oxygen dependence and death. Material and methods. There were 123 patients with COVID-19 with pneumonia under observation. All patients were examined and treated in accordance with the Order of the Ministry of Health of Ukraine No. 722 dated 28.03.2020. The eNOS content in the patients’ serum was determined by enzyme-linked immunosorbent assay. Results. It was found that the content of eNOS in the blood serum of patients with COVID-19 with pneumonia at the time of hospitalization was 9.0 [7.0; 12.0] days lower (p < 0.001) than in healthy subjects. The development of oxygen dependence in patients with COVID-19 with pneumonia was accompanied by worsening of endothelial dysfunction and procoagulant changes, which was confirmed by a decrease in the content of eNOS in the blood serum (p < 0.001), an increase in the level of fibrinogen (p < 0.05) and D-dimer (p < 0.05). The threshold level of eNOS in the blood serum ≤327.09 pg/ml (AUC = 0.861, p < 0.001) was predictive of the onset of oxygen dependence. In patients with COVID-19 with pneumonia who subsequently died, at the time of hospitalization, eNOS levels were lower (p < 0.001) than in patients who recovered, which was combined with a higher level of D-dimer (p < 0.05) and its more frequent increase (p = 0.04) compared with patients who recovered. The eNOS content in the blood serum of patients with COVID-19 with pneumonia was correlated (p < 0.05) not only with the lethal outcome of the disease, but also with the formation of thrombotic complications, which occurred more often in patients with COVID-19 with pneumonia in the event of an adverse outcome (p = 0.0001). The threshold level of eNOS in the blood serum ≤201.75 pg/ml (AUC = 0.892, p < 0.001) was indicative of a high probability of death. Мета роботи – дослідити вміст eNOS у сироватці крові хворих на коронавірусну хворобу (COVID-19) із пневмонією у взаємозв’язку з параметрами гемостазу та з’ясувати її прогностичне значення під час оцінювання ризику розвитку кисневої залежності та летального наслідку. Матеріали і методи. Під спостереженням перебували 123 хворих на COVID-19 із пневмонією. Всі пацієнти обстежені та одержали лікування відповідно до Наказу МОЗ України від 28.03.2020 р. № 722. У сироватці крові хворих визначено вміст eNOS імуноферментним методом. Результати. Встановлено, що вміст eNOS в сироватці крові хворих на COVID-19 із пневмонією на час госпіталізації (на 9,0 [7,0; 12,0] день хвороби) нижчий (р < 0,001), ніж у здорових осіб. Розвиток кисневої залежності у хворих на COVID-19 із пневмонією супроводжувався поглибленням ендотеліальної дисфункції та прокоагулянтними змінами, що підтверджувало зниження вмісту eNOS у сироватці крові (р < 0,001), підвищення рівня фібриногену (р < 0,05) та D-димеру (р < 0,05). Межовий рівень eNOS у сироватці крові ≤327,09 pg/ml (AUC = 0,861, p < 0,001) мав прогностичне значення щодо виникнення кисневої залежності. У хворих на COVID-19 із пневмонією, які надалі померли, на час госпіталізації вміст eNOS був нижчим (р < 0,001), ніж у пацієнтів, які одужали; це поєднувалося з вищим рівнем D-димеру (р < 0,05) і частішим його підвищенням (р = 0,04) порівняно із тими, хто одужав. Вміст eNOS у сироватці крові хворих на COVID-19 із пневмонією мав кореляцію (р < 0,05) не лише з летальним наслідком хвороби, але і з формуванням тромботичних ускладнень, що частіше у хворих на COVID-19 із пневмонією фіксували в разі несприятливого наслідку (р = 0,0001). Межовий рівень eNOS у сироватці крові ≤201,75 pg/ml (AUC = 0,892, p < 0,001) свідчив про високу імовірність летального наслідку.
Вміст ендотеліальної NO-синтази в сироватці крові хворих на коронавірусну хворобу (COVID-19) із пневмонією у взаємозв’язку з параметрами гемостазу залежно від клінічного перебігу та її прогностичне значення
Keywords: coronavirus disease; COVID-19; pneumonia; endothelial dysfunction; hemostasis; diagnosis; prognosis; коронавірусна хвороба; пневмонія; ендотеліальна дисфункція; гемостаз; діагностика; прогноз